Novel characterization of landscape‐level variability in historical vegetation structure. Issue 5 (1st July 2015) - Collins, Brandon M.; Lydersen, Jamie M.; Everett, Richard G.; Fry, Danny L.; Stephens, Scott L.
Abstract : We analyzed historical timber inventory data collected systematically across a large mixed‐conifer‐dominated landscape to gain insight into the interaction between disturbances and vegetation structure and composition prior to 20th century land management practices. Using records from over 20 000 trees, we quantified historical vegetation structure and composition for nine distinct vegetation groups. Our findings highlight some key aspects of forest structure under an intact disturbance regime: (1) forests were low density, with mean live basal area and tree density ranging from 8–30 m 2 /ha and 25–79 trees/ha, respectively; (2) understory and overstory structure and composition varied considerably across the landscape; and (3) elevational gradients largely explained variability in forest structure over the landscape. Furthermore, the presence of large trees across most of the surveyed area suggests that extensive stand‐replacing disturbances were rare in these forests. The vegetation structure and composition characteristics we quantified, along with evidence of largely elevational control on these characteristics, can provide guidance for restoration efforts in similar forests.